Prevention of postoperative surgical wound complications in ankle and distal tibia fractures: results of Incisional Negative Pressure Wound Therapy - Canton, Gianluca; Fattori, Roberto; Pinzani, Emanuele; Monticelli, Luca; Ratti, Chiara; Murena, Luigi (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: complications in surgical wound healing represent the main postoperative complication in ankle and distal tibia fractures. Whereas the use of Incisional Negative Pressure Wound Therapy (INPWT) is recognized to have a role in wound complications prevention in prosthetic surgery, literature about its use in trauma surgery is scarce. The aim of this study was to compare the effectiveness of INWPT with a conventional dressing in order to prevent surgical wound complications in ankle and distal tibia fractures. Methods: The study population included patients over 65 years as well as patients under 65 years considered at risk for wound complications (smokers, obese, affected by diabetes), who underwent ORIF for bi/tri-malleolar ankle fractures or distal tibia (pilon) fractures. After surgery, patients were randomized to receive a conventional dressing or INPWT. Complications in surgical wound healing were classified in major (requiring surgical intervention) and minor complications. Results: 65 patients were included in the study. The rate of minor and major complications between the two groups was not significantly different, although a positive trend towards a lower minor complications rate was noted in the INPWT group (12.6% vs 34.7%). No complications or complaints were reported for the INPWT device. Conclusions: INPWT proved to be safe, well-tolerated and showed promising results in preventing surgical wound complications in ankle and distal tibia fractures.